Reference-less Method for Computing the Transmission Matrix of a Multimode Fiber - N'Gom, Moussa; Norris, Theodore B.; Michielssen, Eric; Nadakuditi, Raj Rao (2018 Optical Fiber Communications Conference and Exposition (OFC), 2018)
A simple imaging system together with complex semidefinite programming is used to generate the transmission matrix of a multimode fiber. The optical design does not contain a reference arm and no interferometric measurements are required. The input signal is modulated in phase to induce strong mode interference at the fiber output.